2023
DOI: 10.1177/03000605231204430
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of scrub typhus with hemorrhage: a case report and literature review

Ziren Chen,
Shi OuYang

Abstract: Scrub typhus (ST) is an acute focal infectious disease that is caused by Orientia tsutsugamushi. The Asia-Pacific region is an area of relatively high incidence. There is a high incidence in China, principally owing to the disease being endemic in the south of the country. The main source of ST infection is rats, which act as reservoirs of infection after being bitten by the chigger mite, and the human population is generally susceptible to the disease. ST can be controlled and treated successfully if antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Studies have shown that scrub typhus often leads to multisystem dysfunction in the second week of onset, manifested as myocardial injury, interstitial pneumonia, meningitis or meningoencephalitis, pancreatitis, abnormal liver function, acute kidney injury, and optic neuritis. [ 6 ] It was uncommon for this patient to manifest symptoms and signs of central nervous system infection from the beginning. This case report aims to guide clinicians in the diagnosis and treatment of scrub typhus with central nervous system involvement as the first symptom.…”
Section: Introductionmentioning
confidence: 98%
“…Studies have shown that scrub typhus often leads to multisystem dysfunction in the second week of onset, manifested as myocardial injury, interstitial pneumonia, meningitis or meningoencephalitis, pancreatitis, abnormal liver function, acute kidney injury, and optic neuritis. [ 6 ] It was uncommon for this patient to manifest symptoms and signs of central nervous system infection from the beginning. This case report aims to guide clinicians in the diagnosis and treatment of scrub typhus with central nervous system involvement as the first symptom.…”
Section: Introductionmentioning
confidence: 98%